2014
DOI: 10.1186/1471-2466-14-178
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of aclidinium bromide/formoterol fumarate fixed-dose combinations compared with individual components and placebo in patients with COPD (ACLIFORM-COPD): a multicentre, randomised study

Abstract: BackgroundAclidinium/formoterol is a twice-daily (BID) fixed-dose combination (FDC) in development for chronic obstructive pulmonary disease (COPD). The efficacy and safety of aclidinium/formoterol versus monotherapy and placebo in patients with COPD was assessed.MethodsIn this 24-week double-blind, parallel-group, active- and placebo-controlled, multicentre Phase III study, patients (≥40 years, post-bronchodilator forced expiratory volume in 1 second [FEV1]/forced vital capacity <70% and FEV1 ≥30% but <80% pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
206
0
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(225 citation statements)
references
References 28 publications
7
206
0
12
Order By: Relevance
“…With non-imputed data, the probabilities of improvement using ACL/FOR were considerably lower versus placebo (70%; mean difference -0.65 units; 95% CrI -3.07 to 1.80), TIO (8%; mean difference 1.78 units; 95% CrI -0.68 to 4.25) and all other combination therapies (\1-6%) than with imputed data. These differences are due to the inclusion of only a single trial reporting outcomes with ACL/FOR versus placebo in the non-imputed data (the ACLIFORM trial [41]) which reported a mean change from baseline in the SGRQ score of -0.65 units; however, the base case analysis also included the AUGMENT trial [42], which reported a considerably larger mean change from baseline of -4.36 units.…”
Section: Weeksmentioning
confidence: 85%
See 1 more Smart Citation
“…With non-imputed data, the probabilities of improvement using ACL/FOR were considerably lower versus placebo (70%; mean difference -0.65 units; 95% CrI -3.07 to 1.80), TIO (8%; mean difference 1.78 units; 95% CrI -0.68 to 4.25) and all other combination therapies (\1-6%) than with imputed data. These differences are due to the inclusion of only a single trial reporting outcomes with ACL/FOR versus placebo in the non-imputed data (the ACLIFORM trial [41]) which reported a mean change from baseline in the SGRQ score of -0.65 units; however, the base case analysis also included the AUGMENT trial [42], which reported a considerably larger mean change from baseline of -4.36 units.…”
Section: Weeksmentioning
confidence: 85%
“…In particular, of the FDCs, only two studies presenting data for ACL/FOR were eligible for inclusion; both of these were 'large' trials (each with[300 patients receiving ACL/FOR [41,42], considerably greater than the previously proposed cut-off for large trials of 100 patients [60]), thereby reducing the likelihood of any distortion of results due to a small study effect [61]. However, the heterogeneity of the studies included in this NMA was not assessed, so the extent of distortion is not known.…”
Section: Discussionmentioning
confidence: 99%
“…These combinations are at least as effective as the simultaneous use of their individual components (possibly via a synergistic effect [137,138]) and significantly improve lung function compared with monotherapy [139][140][141][142][143][144][145]. A positive effect on exercise tolerance has also been demonstrated for indacaterolglycopyrronium and vilanterol-umeclidinium compared with placebo [146,147], although the magnitude of this effect was less when compared to monotherapy with tiotropium.…”
Section: Treatmentmentioning
confidence: 96%
“…103 One clinical study involving subjects with some cardiovascular comorbidities (ACLIFORM-COPD trial) has found no conclusive evidence of significant safety concerns from aclidinium use (in combination with formoterol). 104 The study found that incidences of severe AEs were <5%, and a potential systemic anticholinergic effect of <3%. Although 4 deaths were recorded in the treatment groups, the study did not report any significant change in ECG pattern.…”
Section: Aclidiniummentioning
confidence: 99%